2021
DOI: 10.1002/col.22679
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing skin color before and after 100‐m sprinting

Abstract: We studied skin color in participants before and after a 100‐m sprint using a Konica Minolta CM‐2600d spectrophotometer. Four body positions (forehead, cheek, neck, and inner forearm) were measured for the approximately 30 students (non‐professional runners) who participated in the experiment. Skin reflectance was measured three times at each position before running and again soon afterward. Analysis of the data showed that average measurement repeatability (mean color difference from the mean [MCDM]) was 0.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…In a previous paper (Jiang et al, 2021) we reported skin color results before and after 100-meter sprinting and found that this sprinting considerably changed the values of the CIELAB red-green 𝑎 * coordinate, while the lightness 𝐿 * and yellow-blue 𝑏 * coordinates remained almost constant. In addition, it was found that the red-green 𝑎 * variation depends on body location.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In a previous paper (Jiang et al, 2021) we reported skin color results before and after 100-meter sprinting and found that this sprinting considerably changed the values of the CIELAB red-green 𝑎 * coordinate, while the lightness 𝐿 * and yellow-blue 𝑏 * coordinates remained almost constant. In addition, it was found that the red-green 𝑎 * variation depends on body location.…”
Section: Introductionmentioning
confidence: 87%
“…(3) ∆𝐸 𝑘 defined by Eq. ( 4) below is the so-called mean color difference from the mean, MCDM, and represents measurement repeatability (Wang et al, 2018;Jiang et al, 2021) for the k-th body location…”
Section: Measured Data Evaluation In Cielab Spacementioning
confidence: 99%